Case report: Successful use of ruxolitinib to treat interstitial pneumonia as an unusual primary presentation in primary myelofibrosis—two birds with one stone - Xiao, Pingping; Dong, Zhigao; Wang, Qingqing; Su, Junnan; Chen, Yongquan; Lin, Yiwan (Frontiers in Oncology, 2024)
BackgroundInterstitial lung disease (ILD) is a rare clinical presentation of primary myelofibrosis (PMF).Case presentationWe report a case of ILD as the main manifestation on admission. A 58-year-old man was diagnosed with PMF owing to worsening anemia following treatment failure for conventional interstitial pneumonia.ResultsAnemia and interstitial pneumonia both significantly improved following treatment with a Janus kinase 2 gene inhibitor. In this report, we discuss the possible mechanisms underlying PMF complicated with ILD.